THE DOMESTIC MARKET OF HOUSING SERVICES: ASSESSMENT, CHARACTERISTICS AND PROBLEMS OF DEVELOPMENT - A. Nagaev (Вестник университета)
The article analyzes the competition of the domestic market housing services, showing the modern features of its formation, revealed problems of its development and control over the provision of housing services.